(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
National Rural Employment Guarantee Act (NREGA) is anIndian job guarantee scheme, enacted by legislation on August 25, 2005. Thescheme provides a legal guarantee for one hundred days of employment in everyfinancial year to adult members of any rural household willing to do publicwork related unskilled manual work at the statutory minimum wage. If they failto do so the govt. has to pay the wages at their homes. The Central governmentoutlay for scheme was ₹40,000 crore (US7.28 billion) in financial year2011-12.